(untitled) (Proceedings of International Conference on Special Education, 2017)
The primary goal of this study was to examine the effectiveness of a multisensory approach to reading intervention for students with reading disability. The researcher used a quasi-experimental design in which the control and reading- intervention groups were systematically assigned. The respondents were chosen using purposive sampling. The participants in the reading intervention group achieved a significantly higher post test score on the dependent variable Word Attack and approached significance on the dependent variable Spelling. Although none of the other posttest measures were statistically significant, all posttest standard measures were higher than their matched pre test scores. In contrast, for participants in the control group, no post test scores were significantly higher while the Sight-word Efficiency post test score was significantly lower than its matched pretest score, indicating significantly poorer performance. The study had two main limitations: 1. The short duration of the reading intervention and 2. Lack of randomization of subjects.